UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL BIJI PINANG (ARECAE SEMEN) TERHADAP PERTUMBUHAN BAKTERI ESCHERICHIA COLI, SHIGELLA DYSENTRIAC, DAN SALMONELLA TYPHI - Realisni Telaumbanua; Ulfayani Mayasari (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2021)
This study aims to determine the characteristic of simplisia areca nut (Arecae semen), the class of compounds antibacterial activity determination of ethanolic extract of areca nut (Arecae semen) against Escherichia coli, Shigella dysentriae, dan Salmonella typhi. The method used is ethanol extract of areca nut obtained from maceration process with ethanol 96%. Antibacterial activity testers by the diffusion method in order to use paper discs against Escherichia coli, Shigella dysentriae, Salmonella thyphi. The results of phytochemical screening showed that the areca seed etanol extract (Aracae semen) contained tannin, flavonoid, alkaloid, saponin, dan triterpenoid. The effect of giving ethanol extract of young area nut Escherichia coli, Shigella dysentriae, dan Salmonella typhi bacteri in marked with the formation of inhibit zone of optimum concentration respectively 150 mg/ml, 300 mg/ml, dan 400 mg/ml with an average diameter of 14.36 mm, 14.16 mm, and 14.23 mm. Ethanol extract of old areca nut to bacteria Escherichia coli, Shigella dysentriae, dan Salmonella typhi in marked with the formation of inhibit zone of optimum concentration respectively 300mg/ml, 400 mg/ml, and 500 mg/ml with an average diameter of 14.46 mm, 14.16 mm and 14.26 mm. Based on the result can be concluded ethanol extract of areca nut (Arecae semen) seeds have antibacterial activity to Escherichia coli, Shigella dysentriae, dan Salmonella typhi. Photochemical screening contains a class of compounds having activity as antibacterial, antidiare, dysentery, and antiparasitic.